PERANCANGAN PASAR MODERN DI KECAMATAN SAMPANG DENGAN PENERAPAN ARSITEKTUR MODERN - Moh. Alif Yahfi; Putri Suryandari; Sri Kurniasih (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2023)
Sampang Regency experiences economic growth every year. It is evident from the data that has been summarized by the gross regional domestic product in 2020 regarding economic growth. Currently Sampang District has 4 traditional markets. However, the view of the people of Sampang city towards traditional markets in Sampang District currently seems rundown. From several discussions with the potential and aspects that exist in the District of Sampang it can be developed by designing a modern market. Applying the concept of modern architecture that emphasizes the function of the building with an arrangement that can provide comfort, safety and cleanliness.